GMO — A New Hope or The Road to Perdition - Wójcikowska, Barbara; Suchańska, Katarzyna (No Limits, 2023)
The use of genetically modified micro-organisms (GMMs), as well as the chemical compounds they produce, has a universal tacit approval. Whereas, the production of food using genetically modified organisms (GMOs), mainly plants, is vehemently opposed. Some argue that GMO foods are harmful and should not be consumed, while others believe that they can do a lot of good, e.g. reduce hunger in countries facing food shortages and improve the living standards in developing countries. What are the actual benefits of GMOs – and do they carry any risks?